Some oribatid mites (Acari, Oribatida) from the State of São Paulo, Brazil - Oliveira,Anibal Ramadan (2001)
A survey was conducted in three sites from northern and mid-eastern regions of the State of São Paulo, Brazil, to determine oribatid mite composition in patches of seasonal semideciduous forest and soybean crop plantation. A list of 52 taxa, 24 at the species level and 28 only at the genus level, is given, 27 of which are new records for the region.